2015
DOI: 10.1111/1467-9477.12061
|View full text |Cite
|
Sign up to set email alerts
|

Are Political Parties More Responsive to Advocacy Groups Mobilising Core Voters or Swing Voters? Political Responsiveness to Citizens' Protest Movements in Swedish Local Governments

Abstract: Political scientists often assume that parties listen to some voters more than others. However, this theoretical perspective has rarely been applied to explain political responsiveness to advocacy groups. This article argues that the type of voter mobilised by protest activities plays a role in determining whether advocacy groups are able to influence political decisions. The explanatory value of this approach is demonstrated by a study of the geographic distribution of school closures among Swedish local gove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…Uba ) and since previous work has shown that Swedish politicians see school shutdowns as situations where citizens tend to make contact (Öhberg & Naurin ). Moreover, school shutdowns are not specifically related to ideological issues in which the Swedish parties have static policy positions (Larsson Taghizadeh ). By using school shutdowns, we can alter in realistic ways whether or not the party's voters make the contact, whether or not there is only a slim majority for the policy in the local parliament, as well as the opinion of the respondent.…”
Section: Methodsmentioning
confidence: 99%
“…Uba ) and since previous work has shown that Swedish politicians see school shutdowns as situations where citizens tend to make contact (Öhberg & Naurin ). Moreover, school shutdowns are not specifically related to ideological issues in which the Swedish parties have static policy positions (Larsson Taghizadeh ). By using school shutdowns, we can alter in realistic ways whether or not the party's voters make the contact, whether or not there is only a slim majority for the policy in the local parliament, as well as the opinion of the respondent.…”
Section: Methodsmentioning
confidence: 99%
“…Indicators of demographic responsiveness. Source: Authors' calculations and cluster analysis using data from the National Statistics Office Dummy variable the core voter model states that political majorities will primarily reward voters who have voted for them before (e.g.,Taghizadeh 2015). The theoretical literature does not speak with one voice, which calls for empirical resolution.…”
mentioning
confidence: 99%